Immune Response Modulation by Vitamin D: Role in Systemic Lupus Erythematosus - Iruretagoyena, Mirentxu; Hirigoyen, Daniela; Naves, Rodrigo; Burgos, Paula Isabel (Frontiers in Immunology, 2015)
Vitamin D plays key roles as a natural immune modulator and has been implicated in the pathophysiology of autoimmune diseases, including systemic lupus erythematosus (SLE). This review presents a summary and analysis of the recent literature regarding immunoregulatory effects of vitamin D as well as its importance in SLE development, clinical severity and possible effects of supplementation in disease treatment.